Hepatitis C Infection: Its Sequelaie and Outcomes – State-of-the-Art Workshop, September 24 to 25, 1998 - Association for Study of the Liver (CASL) (Canadian Journal of Gastroenterology)
This report summarizes a state-of the- art workshop held in September 1998 on the “Natural History and Outcome of Hepatitis C Infection”. Sixteen Canadian and two internationally renowned hepatologists were invited. A practical classification of HCV infection served as a framework for the meeting. The concepts of modelling of chronic disease, the epidemiology of HCV infection before the introduction of anti-HCV testing, and the outcome of various forms of chronic hepatitis C in adults and children were presented. Lectures on the outcome of HCV cirrhosis, hepatocellular carcinoma, the role of liver transplantation, the influence of host factors on outcome, iron overload in chronic hepatitis C and possible modification of the natural history by antiviral therapy were followed by discussion and consensus statements pertaining to each presentation. “The European Experience in Assessing Chronic Hepatitis C” was presented by Prof G Dusheiko from the United Kingdom, and Prof Leonard Seeff from the National Institutes of Health (United States) presented “The Epidemiology and Outcome of Hepatitis C Infection in the United States and the World”.